RELATIONSHIP BETWEEN SPORTS FACILITIES AND PARTICIPATION IN SPORTS IN SELECTED NIGERIAN UNIVERSITIES (1989)
The focus of this thesis was based on the examination of the relationship between sports facilities and sports participation in selected Nigerian Universities. In conducting this research, certain issues were raised. These included the adequacy or otherwise of the available facilities, the maintenance levels of these facilities and the participation levels in sports by both the students and staff of the selected Universities. The null hypothesis stated that there would be no significant relationship between the available sports facilities and sports participation in the selected Nigerian Universities. The main and sub-hypotheses were tested using the Spearman Rank-Order Correlation (r s), the chi-square (x2), and percentages in order to accept or reject the hypotheses. The analyses were based on well presented data on the thirteen universally played sports in Nigerian Universities Games Association (NUGA). The results showed high and positive correlation of the variables. All the sub-hypotheses were accepted. The findings showed that sports facilities in these universities were inadequate and substandard while the maintenance levels of the facilities were unsatisfactory. The participation levels in sports were also found to be low. Based on these findings, it was concluded that there was no significant relationship between the available sports facilities and sports participation in the selected Nigerian Universities. It was therefore recommended that Nigerian Universities should provide adequate and standard sports facilities in their campuses. The maintenance of these facilities should also be a priority to every University. These were considered as vital factors to effective participation in University sports.